(f o g)(-2) f(x) = x^2 - 2x g(x) = 3x + 2 Do I have to plug in (-2) in g, and then plug that number into f? Or do i have to plug in (-2) to both functions and then plug in what I got for g into f? im confused Is the answer 24?
Follow Math Help Forum on Facebook and Google+
Originally Posted by NeedHelp18 (f o g)(-2) f(x) = x^2 - 2x g(x) = 3x + 2 Do I have to plug in (-2) in g, and then plug that number into f? That's the correct one Basically, $\displaystyle (f \circ g)(x)=f(g(x))$ Is the answer 24?
View Tag Cloud